2001
DOI: 10.1161/hq0901.094500
|View full text |Cite
|
Sign up to set email alerts
|

LR11, a Mosaic LDL Receptor Family Member, Mediates the Uptake of ApoE-Rich Lipoproteins In Vitro

Abstract: Abstract-Since the molecular identification of the low density lipoprotein receptor (LDLR), an ever increasing number of related proteins have been discovered. These receptors belonging to the LDLR family are thought to play key roles in lipoprotein metabolism in a variety of tissues, including the arterial wall. We have discovered that the expression of a 250-kDa mosaic LDLR-related protein, which we termed LR11 for the presence of 11 LDLR ligand-binding repeats, is markedly induced in smooth muscle cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…These results raised the question of whether sorLA could mediate the internalization of cell surface APP and thereby also reduce the processing of APP into sAPP and A␤. It has been shown that sorLA is capable of mediating endocytosis (Jacobsen et al, 2001) and binds apolipoprotein E-rich lipoproteins and mediate their uptake (Taira et al, 2001). When we investigated uptake of APP from the cell surface, however, we found that APP internalization is independent of sorLA.…”
Section: Discussionmentioning
confidence: 99%
“…These results raised the question of whether sorLA could mediate the internalization of cell surface APP and thereby also reduce the processing of APP into sAPP and A␤. It has been shown that sorLA is capable of mediating endocytosis (Jacobsen et al, 2001) and binds apolipoprotein E-rich lipoproteins and mediate their uptake (Taira et al, 2001). When we investigated uptake of APP from the cell surface, however, we found that APP internalization is independent of sorLA.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 For analysis of phosphorylated extracellular signal-regulated kinase (ERK), cells were starved for 48 hours in 0.3% FBS-DMEM followed by the addition of platelet-derived growth factor (PDGF)-BB (R&D Systems) at 10 ng/mL for 10 minutes. For the analysis of cell-surface urokinasetype plasminogen activator receptor (uPAR), cells were treated with 0.5 U/mL of phosphatidylinositol-specific phospholipase C (SigmaAldrich) for 2 hours and the media recovered.…”
Section: Blot Analyses and Immunocytochemistrymentioning
confidence: 99%
“…For the analysis of cell-surface urokinasetype plasminogen activator receptor (uPAR), cells were treated with 0.5 U/mL of phosphatidylinositol-specific phospholipase C (SigmaAldrich) for 2 hours and the media recovered. For inhibition assays, cells were starved for 24 hours, and the medium was changed to 10% FBS-DMEM containing receptor-associated protein (RAP) (10 g/mL), anti-LR11 antibody (1:2 dilution), 12 or apolipoprotein E (apoE; 50 g/mL, Cosmo Bio) for 24 hours. Equal amounts of membrane protein or phosphatidylinositol-specific phospholipase C (PI-PLC)-conditioned medium were subjected to SDS-PAGE under reducing (Western blot) and nonreducing (ligand blot) conditions.…”
Section: Blot Analyses and Immunocytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Other ligands of SorLA include lipoproteins (12), PDGF-BB (23), and GDNF (24). In accordance with the multiple ligands, SorLA also seems to be involved in several functions including protein sorting (25), lipoprotein uptake (26), smooth muscle cell migration, and the development of atherosclerosis (27), but so far no signaling cascade has been identified. Recently, SorLA was identified to be involved in trafficking APP in neuronal cells.…”
mentioning
confidence: 98%